Improving Antimicrobial Activity of Carbon/Gelatin Composite by Ce(III) - Tengfei Yu; Yang Guo; Bin Ning; Peiyi Gao; Yaqin Huang (International Journal of Polymer Science)
Carbon/gelatin/Ce (CGCe) composite was prepared with high antimicrobial activity. And the structure, thermal property, and antimicrobial activity of the composite were investigated. The research results showed that CGCe has a higher thermal property and antimicrobial activity against S. aureus and E. coli compared with CG. The influences of molecular weight of gelatin, pH, and concentration of Ce (III) on the antimicrobial activity were discussed, and the IC50, MIC, and MBC against S. aureus of CGCe are 185 μm·mL-1, 525 μm·mLl-1, and 700 μm·mL-1, respectively, and the IC50, MIC, and MBC against E. coli of CGCe are 255 μm·mL-1, 700 μm·mL-1, and 1050 μm·mL-1, respectively.